Mapping the extent of unhealthy food advertising around schools in Tāmaki Makaurau/Auckland - Karolina Kneller; Kelly Garton; Daniel J. Exeter; Victoria Egli (Kōtuitui)
Advertisements promoting energy-dense, nutrient-poor food and drinks influence children’s dietary choice and preference and are pervasive in children’s environments across Aotearoa, New Zealand. Using a combination of datasets from separate studies, this research seeks to describe the extent of children’s unhealthy food/drink advertising exposure in all primary and intermediate school food zones (n = 381) in Tāmaki Makaurau, Auckland, and assess whether this exposure correlates with indicators of neighbourhood deprivation. To achieve this, we developed a simple advertising exposure score using images of advertising collected from Google Street View, and investigated its spatial correlation with indicators of neighbourhood deprivation. Outdoor advertising was present in proximity to 61.9% of the sampled schools (n = 236); of which 83.1% of adverts promoted unhealthy food and/or drinks (n = 2669). Advertising exposure increased statistically significantly with neighbourhood deprivation (p < 0.05). The results show a clear need for policy intervention that regulates and limits unhealthy food/drink advertising around schools in New Zealand. The advertising score proved a useful, easy to understand tool to measure and visualise children’s potential exposure to unhealthy food/drink advertising. The score may be used to increase community awareness of the ubiquity of unhealthy advertising in children’s neighbourhoods and advocate for policy change.Practitioner pointsAdvertising present in the vicinity of 62% of Auckland schools; 83% of adverts promoted unhealthy food and/or drinksNovel advertising score assesses the spatial distribution of unhealthy advertising exposure.Advertising exposure score is significantly related to neighbourhood deprivation.Findings show the need for policy action to limit children’s advertising exposure around their schools in NZ.